Accounting amortization for biological assets - Arévalo Orjuela, Elena Marcela
This is a review article concerning the International Financial Reporting Standards (IFRS), specifically IAS 41, Agriculture; whose objective is to prescribe the accounting treatment, the rendering of the financial statements and the information and disclosure related to the agricultural activity. A contribution of great magnitude especially for the agricultural sector is the so-called "biological assets", as defined in IAS 41 as "living plants or animals". Since in traditional accounting the treatment given to these is ambiguous and it is not recognized that they are subject to a biological transformation (e.g. own growing, degenerating, production and/or procreating) which produces qualitative and / or quantitative changes in those assets, and this feature can generate uncertainty or conflicts when traditional accounting methods are applied". In this case, the historical costs that do not provide enough financial information that is adjusted to the value of foreign markets. Among one of the most representative changes made by IAS 41, is the application of fair value to items such as biological assets, a measurement criterion that has not been used by accounting professionals in the country and that is of great importance since it specifically regulates the accounting of the most important sector of the economy such as agriculture, therefore the accounting profession must try to make the accounting recognition the most adjusted to reality, understandable, comparable in international markets.